Brown adipose tissue derived ANGPTL4 controls glucose and lipid metabolism and regulates thermogenesis - Abhishek K. Singh (Molecular Metabolism, 2018)
Objectives: Brown adipose tissue (BAT) controls triglyceride-rich lipoprotein (TRL) catabolism. This process is mediated by the lipoprotein lipase (LPL), an enzyme that catalyzed the hydrolysis of triglyceride (TAG) in glycerol and fatty acids (FA), which are burned to generate heat. LPL activity is regulated by angiopoietin-like 4 (ANGPTL4), a secretory protein produced in adipose tissues (AT), liver, kidney, and muscle. While the role of ANGPTL4 in regulating lipoprotein metabolism is well established, the specific contribution of BAT derived ANGPTL4 in controlling lipid and glucose homeostasis is not well understood. Methods and results: We generated a novel mouse model lacking ANGPTL4 specifically in brown adipose tissue (BAT-KO). Here, we report that specific deletion of ANGPTL4 in BAT results in enhanced LPL activity, circulating TAG clearance and thermogenesis. Absence of ANGPTL4 in BAT increased FA oxidation and reduced FA synthesis. Importantly, we observed that absence of ANGPTL4 in BAT leads to a remarkable improvement in glucose tolerance in short-term HFD feeding. Conclusion: Our findings demonstrate an important role of BAT derived ANGPTL4 in regulating lipoprotein metabolism, whole-body lipid and glucose metabolism, and thermogenesis during acute cold exposure. Keywords: ANGPTL4, Obesity, Lipoprotein metabolism, Glucose tolerance, Thermogenesis